PENGARUH PENERAPAN METODE ANDRAGOGI TERHADAP TINGKAT PENDIDIKAN, KEAKTIFAN KERJA DAN HASIL PANEN PADI PADA SEKOLAH LAPANG PENGENDALIAN HAMA TERPADU (SLPHT) DI DISTRIK AIMAS KABUPATEN SORONG - SUTARDI SUTARDI; VIRMAN VIRMAN (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
This study examines the effect of the application of the method to focus Andragogy the level of education, active labor and the harvest on Integrated Pest Management Field School (FFS) in District Aimas Sorong Regency. Implementation of this research was conducted in three groups of farmers in the district forward Aimas ie farmer groups of 25 people, farmer groups and the border of the farmer 25 farmer groups Rukun Wargi 25 people that totaled 75 people. This research is experimental real. For the regression test results of this study indicate that there is a significant contribution between andragogy methods the education level of 0.4%, a simple regression test results showed that, Andragogy method to work activeness of 1.2%, while for methods of andragogy against varabel harvest rice result of 45.7%. Based on the results of this study concluded that there is the influence of the simultaneous application of the method Andragogy the level of education, active labor and the harvest on Integrated Pest Management Field School (FFS) in District Aimas Sorong Regency.